HUBUNGAN MUTU PELAYANAN PENDAFTARAN ONLINEPASIEN RAWAT JALAN DENGAN KEPUASAN PASIEN JKN DI RSUD KABUPATEN TEMANGGUNG - NURUL WAHYU ANGGRAENI; Trismianto Asmo Sutrisno; Sri Sri Sugiarsi (Indonesian Journal of Health Information Management, 2024)
Background:The quality of online registration services is important because it is a form of consumer assessment of the level of service received and the level of service expected. Objective: This study aimed to analyze the relationship between the quality of online registration services for outpatients and the satisfaction of JKN patients at the Hospital of Temanggung Regency. Methods: This research was an analytical research with a quantitative approach and a cross-sectional research design. The number of samples in this study were 99 people selected using simple random sampling technique. Retrieval of data through interviews using a questionnaire that had previously been tested for validity and reliability.Results: The results of the chi-square analysis showed that there was a relationship between the quality of outpatient online registration services and JKN patient satisfaction (p value 0.000 <0.05). Conclusion: The study concluded that there was a relationship between the quality of outpatient online registration services and the satisfaction of JKN patients at the Hospital of Temanggung Regency.